Exploring perceived barriers and facilitators to mental health help-seeking in adolescents: a systematic literature review. Issue 2 (3rd April 2022) - Barrow, Emma; Thomas, George
ABSTRACT: Despite high incidence rates of adolescent mental health difficulties, only a small minority of young people access support. To explore this gap, this systematic literature review (SLR) synthesises existing research exploring barriers and facilitators to help-seeking. The authors identified 12 eligible studies that were critically appraised: seven provided quantitative data, two provided qualitative data and three employed mixed-methods approaches. Four global barrier themes were identified, namely: stigma; practical barriers; negative attitudes and perceptions; and knowledge barriers. Two global facilitator themes also emerged, including: mental health literacy; and wellbeing and community factors. The findings highlight important implications for improving help-seeking behaviours in adolescents, including increasing mental health support in school. The findings are discussed relative to the role of the educational psychologist (EP), as EPs are well-positioned to support universal and targeted approaches that endeavour to reduce stigma, enhance service accessibility, promote connectedness, and improve mental health literacy.